STRATEGI DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF PADA UKM - Rodhiah, Rodhiah; Bravo, Christiandinata Tjandra (Transpublika Publisher, 2023)
Competitive Strategy is a strategy that focuses on management's plan to compete successfully. The main goal is to attract customers, overcome competitive pressures, and strengthen the company's market position. The activity partner is engaged in the business of handicraft creative products located in Serang, Banten province. In its activities facing problems especially in terms of competitive advantage. PKM aims to assist partners in efforts to increase knowledge about efforts to increase competitive advantage. The method of activities carried out with training related to competitive advantage presented in the form of PPT includes: understanding of competitive advantage, components in competitive advantage, types of competitive advantage and so on. The training was conducted online assisted by 2 students. The results of the activity show that the implementation has run smoothly, partners are enthusiastic about receiving the material presented, as evidenced by the two-way communication and discussion between partners and the PKM team, this activity can increase partner interviews in increasing the competitive advantage of the products sold. PKM outputs are in the form of publications to journals and IPR.